A Quaternary very young juvenile Tapirus Brisson, 1762 (Mammalia, Perissodactyla) from a cave deposit in northern Brazil: taxonomy and taphonomy - Gasparini, Germán Mariano (2015)
During fieldworks carried out from 2009 to 2013 in Aurora do Tocantins (northern Brazil), three isolated deciduous teeth of Tapirus were recovered. Those fossils come from a sedimentary deposit of presumed Late Pleistocene–early Holocene age in a karstic cave. This contribution aims to present a new locality of fossil Tapirus from northern Brazil, describe for the first time deciduous fossil teeth for South American Tapirus and evaluate the taphonomic aspects of those fossils. The specimens probably belong to the same individual due to there are no repeated teeth and they have the same wear pattern. Furthermore, the crowns of those teeth show no evidence of abrasion produced by transport. However, some abrasion is observed on the borders of the pulp chamber of teeth. These polishing are probably resulting of a very short transport (parautochthonous). These specimens are the only record of Tapiridae in Gruta do Urso cave; due to correspond to isolated and deciduous teeth, its identification to species level was not possible. There is not yet clear evidence that may indicate the kind of death of the individual studied here.